Crude Protein and Crude of Fiber Benggala [Panicum Maximum] and Elephant [Pennisetum Purpureum] Grasses on Drought Stress Condition - Purbajanti, ED; Anwar, S; Widyati, S; Kusmiyati, F (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
Knowledge of crop response to water is essential for proper irrigation management. Research was conducted at Forage Crop Laboratory of Animal Nutrition Department, Faculty Of Animal Husbandry, Diponegoro University during 9 month trying two type grass that were benggala ( Panicum maximum) and elephant ( Pennisetum purpureum) with treatment of the following dry stres : S0 = control, without stress; S1 = 1 times drought stress, S2 = 2 times drought stress , and S3 = 3 times drought stress by lay out of complete random design( factorial pattern). Parameter perceived were( 1) forage production , (2) dry matter production, (3) percentage of crude protein, and (4) percentage of crude fibre. Data collected to be analysed by analysis of varians continued with Duncan multiple range test. Result of research indicate that forage production of elephant grass (103,79 g/pot) bigger than benggala (53,08 g/pot). Dry matter production of elephant grass was 18,77 g/pot higher than benggala grass( 14,54 g/pot). Drought stres do not affect to forage production also dry matter production : Percentage of crude protein of benggala grass (9,10%) higher than elephant grass (7,02%), while percentage crude fibre of benggala grass (35,64%) higher than elephant grass (31,67%). Drought stres do not influence percentage of crude protein and crude fibre of benggala and elephant grasses. Conclusion from research were (1) elephant grass have higher forage production and dry matter production than benggala grass (2) percentage of crude protein and crude fibre of benggala grass higher than elephant grass, (3) drought stres do not affect to forage production , dry matter production, percentage of crude protein and crude fibre. (Animal Production 11(2): 109-115 (2009) Key Words : crude protein, fiber, drought stress